2007
DOI: 10.1002/pssa.200723078
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pelletization pressure on the structural and transport properties of TlCaBaCuO superconductors

Abstract: An investigation is reported of the effects of pelletization pressure on the structural and transport properties of polycrystalline TlCaBaCuO samples with nominal composition of Tl2Ba2Ca2Cu3O10–x . The measurements reveal the following interesting results as the pelletization pressure increases: (1) the volume fraction of self‐formed Tl‐2212 phase decreases and the amount of target Tl‐2223 phase increases; and (2) the links between grains become stronger. Consequently, energy dissipation on grain boundaries de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…It was also observed that the zero resistance temperature T c (off) increased and the transition width decreased with increasing pellet formation pressure. Transport critical currents of samples increased with increasing temperature as a consequence of improved intergranular couplings [7].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…It was also observed that the zero resistance temperature T c (off) increased and the transition width decreased with increasing pellet formation pressure. Transport critical currents of samples increased with increasing temperature as a consequence of improved intergranular couplings [7].…”
Section: Introductionmentioning
confidence: 98%
“…Beside Bi-based superconductors, Topal [7] have investigated the effect of compaction pressure on the structural and electrical properties of TlCaBaCuO superconducting materials. The porosity and the volume fraction of the Tl-2212 phase in the samples prepared with a nominal composition of Tl 2 Ba 2 Ca 2 Cu 3 O 10−δ were found to decrease and the Tl-2223 phase content increased with increasing compaction pressure in the above study.…”
Section: Introductionmentioning
confidence: 99%
“…One can see a small field dependence. On the other hand, the V – I characteristics of the oxygenated sample reveal that the logarithmic plots of the V – I data sets were found to be linear (above 10 µV), typical for polycrystalline HTSC 28 (Fig. 5b).…”
Section: Resultsmentioning
confidence: 96%